2019 IEEE Photonics Conference (IPC) 2019
DOI: 10.1109/ipcon.2019.8908417
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Wireless Optical Communications at 100 Mb/s using Integrated Dual-Color Micro-LEDs

Abstract: Integrated blue-violet and blue-green micro-LED arrays, fabricated via a transfer printing method, were employed to demonstrate wavelength division multiplexing underwater data transmission at 100 Mb/s over up to 9 attenuation lengths in a 1.5 m long water tank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to combat the impact of the dead-time, arrays of SPADs working in parallel are used, also known as silicon photomultipliers (SiPM) or multi-pixel photon counter (MPPC), such that some of SPADs within SiPM are available for responding the incident light during the dead time [19][20][21]. It has been recently shown that SiPM is able to significantly enhance the sensitivity of the optical receiver in IM-DD UWOC systems [20,[22][23][24]. Therefore, SiPM can be a promising candidate in the realization of highly sensitive detection in the DPSK UWOC system.…”
Section: Introductionmentioning
confidence: 99%
“…In order to combat the impact of the dead-time, arrays of SPADs working in parallel are used, also known as silicon photomultipliers (SiPM) or multi-pixel photon counter (MPPC), such that some of SPADs within SiPM are available for responding the incident light during the dead time [19][20][21]. It has been recently shown that SiPM is able to significantly enhance the sensitivity of the optical receiver in IM-DD UWOC systems [20,[22][23][24]. Therefore, SiPM can be a promising candidate in the realization of highly sensitive detection in the DPSK UWOC system.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], the communication rate by OOK modulation is much higher, but the photon utilization efficiency is relatively low. The communication rate of SPAD arrays is very high (1 Gbps) in analog output mode [8] and can reach up to 100 Mbps in digital-output mode [9]. However, SPAD arrays have a low detection sensitivity and require several hundred to several thousand photons to deliver one bit.…”
mentioning
confidence: 99%